The formation and orientation of brush border vesicles from rat duodenal mucosa. - Hearn, P; Russell, R; Farmer, J (1981)
An electron-microscopic study of various fractions taken during a newly developed method for preparation of brush border vesicles from rat duodenum, has shown that vesiculation of microvilli can occur in situ on the brush border membrane. This mode of formation ensures that the vesicle membranes are oriented as in vivo and that they are "right-side-out". The disruption of core protein-fibres appears to be a prerequisite for vesicle formation.